Comparison of the Agronomic, Cytological, Grain Protein Characteristics, as Well as Transcriptomic Profile of Two Wheat Lines Derived From Wild Emmer - Gong, Fangyi; Qi, Tiangang; Zhang, Tian; Lu, Yusen; Liu, Jia; Zhong, Xiaoying; He, Jingshu; Li, Yunfang; Zheng, Youliang; Liu, Dengcai; Huang, Lin; Wu, Bihua (Frontiers in Genetics, 2022)
Two wheat advanced lines BAd7-209 and BAd23-1 without the functional gene GPC-B1 were obtained from a cross between common wheat cultivar chuannong16 (CN16) and wild emmer wheat accession D97 (D97). BAd7-209 showed superior quality parameters than those of BAd23-1 and CN16. We found that the composition of glutenins and gliadins in BAd7-209 and BAd23-1 were similar, whereas BAd7-209 had higher amount of glutenins and gliadins than those of BAd23-1. RNA-seq analysis on developing grains of BAd7-209 and BAd23-1 as well as their parents revealed 382 differentially expressed genes (DEGs) between the high GPC (D97 + BAd7-209) and the low GPC (CN16 + BAd23-1) groups. DEGs were mainly associated with protein processing in endoplasmic reticulum, trans-Golgi network and the regulation of the transcription of gluten genes. Our results indicate that NAC, Bzip, Dof and MYB TFs may be involved in regulation of the expression of glutenin and gliadin genes. The protein processing in endoplasmic reticulum and trans-Golgi network are important regulation pathways that contribute to grain protein accumulation.